Organizing for War : France, 1870-1914 - Chrastil, Rachel (Book collections on Project MUSE., 2010)
By the end of the Franco-Prussian War (1870--71), Germany occupied one third of French territory, thousands of Alsatians and Lorrainers had flooded into France, and 140,000 French soldiers had died. France's crushing defeat in the most significant European armed conflict between the Napoleonic wars and World War I cast long shadows over military garrisons, meeting halls, and kitchen tables throughout the nation. Until now, no study has adequately addressed the complex, lasting effects of the war on the lives of ordinary French men and women. In this stimulating new book, Rachel Chrastil provid.